The Students’ Perceptions of Mathematics on Learning Online at STKIP Tunas Palapa Central Lampung - Rini, Ambar Prisetia (CV. Creative Tugu Pena, 2021)
The Covid-19 pandemic has brought big changes to the world, including in the field of education. In an attempt to contain the spread of COVID-19, the Minister of Education and Culture has made a policy regarding the teaching and learning process that is implemented online. The purpose of this study was to determine students' perceptions of online learning during the Covid-19 pandemic. This study used a quantitative descriptive analysis method with a research instrument in the form of a questionnaire distributed online by google form. The sample in this study were 40 students from the STMIK Dharma Wacana Metro in Information Technology Study Program who had been involved in online learning during the Covid-19 pandemic. The results showed that 100% students implemented online learning in the first semester of the 2020/2021 academic year. The majority of students prefer offline learning in face-to-face classes compared to online learning. The obstacles faced during online lectures make students want a renewal of the education system for subsequent lectures. The government needs to ensure the availability of adequate internet network access in all regions and college provide subsidized internet quota for students. So, the lecture activities can be run smoothly and as expected. Keywords: Students’ Perceptions, Learning Online, Learning Mathematic